A multidisciplinary team case management approach reduces the burden of frequent asthma admissions. Issue 3 (29th July 2016) - Burke, Hannah; Davis, Jenny; Evans, Sian; Flower, Laura; Tan, Andrew; Kurukulaaratchy, Ramesh J.
Up to 10% of asthmatics have "difficult asthma"; however, they account for 80% of asthma-related expenditure and run the highest risk of acute severe exacerbations. An estimated 75% of admissions for asthma are avoidable. Guidelines advise that these patients be managed by an experienced specialist multidisciplinary team (MDT). We aimed to assess the impact of a case management strategy delivered via specialist MDTs on acute healthcare utilisation of patients with frequent asthma admissions. An MDT (consultant, specialist nurse, physiotherapist and psychologist) case management strategy was introduced in 2010 at University Hospital Southampton Foundation Trust (Southampton, UK) to support patients with frequent asthma admissions during admission and then in clinic. To assess efficacy, we systematically searched the hospital database for patients acutely admitted for asthma on two or more occasions in 2010, 2011 and 2012. Data were collected retrospectively covering patient demographics, admission details, asthma severity and comorbidity. From 2010 to 2012, 84 patients were admitted on two or more occasions per year (80% female, mean body mass index 31 kg·m −2 and 55% psychological comorbidity). After introducing an MDT approach repeat asthma admissions fell by 33% from 127 in 2010 to 84 in 2012 (p=0.0004). In addition, bed days fell by 52% from 895 in 2010 to 430 in 2010 (p=0.015). An MDT case management approach significantly reduces hospitalisation in difficult asthma patients with prior frequent admission. MDT case management approach significantly reduces hospitalisation in asthma patients with prior frequent admission http://ow.ly/7iOI3016277